2017
DOI: 10.1016/j.bios.2016.09.067
|View full text |Cite
|
Sign up to set email alerts
|

A unique iridium(III) complex-based chemosensor for multi-signal detection and multi-channel imaging of hypochlorous acid in liver injury

Abstract: Although hypochlorous acid (HOCl) has long been associated with a number of inflammatory diseases in mammalian bodies, the functions of HOCl in specific organs at abnormal conditions, such as liver injury, remain unclear due to its high reactivity and the lack of effective methods for its detection. Herein, a unique Ir(III) complex-based chemosensor, Ir-Fc, was developed for highly sensitive and selective detection of HOCl. Ir-Fc was designed by incorporating a ferrocene (Fc) quencher to a Ir(III) complex thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 58 publications
4
48
0
Order By: Relevance
“…[22] Amongt hese metal complexes, cyclometalated Ir III complexes are particularly intriguing owing to their several favorable photophysical properties for luminescence bioassays: [23] i) tunable luminescence emissions with variations of coordinativel igands;i i) high stability under ambient conditions and bright luminescence emissions;i ii)large Stokes shifts;i v) resistancet op hotobleaching; v) low cytotoxicity;v i) long emission lifetime; and vii)cell organelle-targetable features. [24] In previous research, we have also confirmed the capability of Ir III complex-based responsive phosphorescence probes for the detection of biomarkers, such as reactive oxygen species, [25] and methylglyoxal in vitro and in vivo. [26] These facts prompted us to design au nique Ir III complex phosphorescence probe for highly sensitived etection of Cys, and for furthers tudies of Cys-mediated redox activities in biological systems.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…[22] Amongt hese metal complexes, cyclometalated Ir III complexes are particularly intriguing owing to their several favorable photophysical properties for luminescence bioassays: [23] i) tunable luminescence emissions with variations of coordinativel igands;i i) high stability under ambient conditions and bright luminescence emissions;i ii)large Stokes shifts;i v) resistancet op hotobleaching; v) low cytotoxicity;v i) long emission lifetime; and vii)cell organelle-targetable features. [24] In previous research, we have also confirmed the capability of Ir III complex-based responsive phosphorescence probes for the detection of biomarkers, such as reactive oxygen species, [25] and methylglyoxal in vitro and in vivo. [26] These facts prompted us to design au nique Ir III complex phosphorescence probe for highly sensitived etection of Cys, and for furthers tudies of Cys-mediated redox activities in biological systems.…”
Section: Introductionsupporting
confidence: 66%
“…Prior to the imaging application, the cytotoxicity of [Ir(ppy) 2 (NTY-bpy)] + towards MCF-7 cells andJ 774A.1 macrophage cells was evaluated by MTT assay and PrestoBlue viability assay, respectively.U pon incubating MCF-7 cells with [Ir(ppy) 2 (NTYbpy)] + at the concentrationso f0 ,1 0, 20, 40, 100,a nd 200 mm, remarkable effects on the cell proliferation weren ot observed ( Figure S20 Chem.E ur.J. 2019,25,[1498][1499][1500][1501][1502][1503][1504][1505][1506] www.chemeurj.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim tration of the complex (10-30 mm)i sn ormally used for cell imaging, the cytotoxicity at these concentrations is negligible.…”
Section: Imaging Of Cys In Live Cellsmentioning
confidence: 99%
“…Herein, we designed and synthesized a novel benzocoumarin-Cu 2+ ensemble based fluorescence chemosensor for the selective detection of biothiols under simulated physiological conditions and in human urine. As described in Scheme 1, the fluorescent ligand (L), as expected, could coordinate with Cu 2+ to form L-Cu 2+ which exhibited nearly no fluorescence owing to the paramagnetic quenching effect of Cu 2+ [50]. The subsequent ensemble L-Cu 2+ would then be the platform for the real-time detection of biothiols with "OFF-ON"response due to higher affinity between biothiols and Cu 2+ .…”
mentioning
confidence: 77%
“…Among them, a Cu 2+ -ensemble based fluorescence chemosensor features simple synthetic route, improved water solubility, a fluorescence "OFF-ON" response pattern as well as desired reversibility [44][45][46]. By the way, our group has been involved in longstanding exploration of the synthesis and application of this class of fluorescence chemosensors [47][48][49][50][51][52][53][54][55][56][57][58][59]. Herein, we designed and synthesized a novel benzocoumarin-Cu 2+ ensemble based fluorescence chemosensor for the selective detection of biothiols under simulated physiological conditions and in human urine.…”
mentioning
confidence: 99%
“…Metal complex-based probes are particularly suitable for lifetime-based imaging in a wide range of targets in cells, as they emit from long-lived, triplet-based excited states that are usually efficiently populated through the heavy-atom effect. For example, some metal complex-based probes can cross the membrane and accumulate in the mitochondria to detect metabolic status in mitochondria of cells33. Ruthenium-based probes have been developed for lifetime-based imaging of the cellular DNA, RNA and oxygen levels2334.…”
Section: Discussionmentioning
confidence: 99%